2022
DOI: 10.1186/s12879-022-07932-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection disclosure, treatment self-efficacy and quality of life in HIV-infected MSM receiving antiretroviral therapy

Abstract: Background Research on the relationship between disclosure of HIV status to male sexual partners (HIV disclosure) and quality of life (QOL) revealed complex and even contradictory results. The impact of HIV disclosure on various domains of QOL and the mediation effect between them are unclear. The purposes of this study were to explore the impact of HIV disclosure on QOL among men who have sex with men (MSM), and whether HIV treatment self-efficacy mediated these relationships. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
1
0
1
Order By: Relevance
“…Previous studies using the same self-efficacy measurement as this study also reported positive correlations between QoL of PLWH and self-efficacy for managing symptoms, getting support/help, and managing fatigue [ 24 ], confirming that self-efficacy is a significant predictor of QoL [ 25 ]. Self-efficacy was associated with better QoL in social relationships and physical and psychological independence, and overall social environment domain [ 40 ], suggesting that self-efficacy can directly influence health promotion behavior. PLWH could experience a range of symptoms owing to HIV infection, medication side effects, and medical complications [ 41 ], and fatigue are a pervasive symptom among PLWH [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using the same self-efficacy measurement as this study also reported positive correlations between QoL of PLWH and self-efficacy for managing symptoms, getting support/help, and managing fatigue [ 24 ], confirming that self-efficacy is a significant predictor of QoL [ 25 ]. Self-efficacy was associated with better QoL in social relationships and physical and psychological independence, and overall social environment domain [ 40 ], suggesting that self-efficacy can directly influence health promotion behavior. PLWH could experience a range of symptoms owing to HIV infection, medication side effects, and medical complications [ 41 ], and fatigue are a pervasive symptom among PLWH [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 Một số yếu tố có khả năng tác động tiêu cực đến chất lượng cuộc sống: người nhiễm HIV/ AIDS bị kỳ thị có điểm chất lượng cuộc sống thấp hơn so với những người nhiễm HIV/AIDS không gặp sự kỳ thị. Kết quả này tương đồng với nhiều nghiên cứu trước đó về vấn đề này.…”
unclassified